Stakeholder involvement in developing LNG as a ship fuel in the Baltic Sea region - Albrecht, Jörg (2015)
New environmental regulations require the shipping industry to reduce its sulphur emissions. The currently most environmentally friendly alternative for ship owners to comply with the regulations is the switch to LNG fuelled vessels which however also requires port developers to invest in the supply of LNG. In order to successfully implement the creation of an LNG infrastructure, various challenges have to be overcome. This study looks at the challenges of LNG as a ship fuel from a stakeholder perspective by conducting a port screening with the aim to assess the current development status of LNG projects and the drivers and impediments behind it. Furthermore, a qualitative research with expert interviews of the most important stakeholder groups gives insight on how stakeholders are involved in the various aspects of LNG development. While several challenges have impeded the introduction of LNG as ship fuel in the past years, by far the biggest issue in the soon future is the development of the oil price that lowers the feasibility of LNG ship fuel compared to oil-depending alternatives. The study also revealed that the potential of local industries and cargo owners to influence the implementation of LNG as ship fuel has been neglected so far. The successful creation of an LNG infrastructure relies on public funding programs. Therefore, policy makers need to have well-elaborated strategies and increase the general perception of LNG among local industries and legal authorities by pointing out the potential of LNG for the whole economy. The results can support policy makers on EU level in their decision of composing an LNG strategy and give interesting insight to involved actors about the stakeholder network. The study was limited to the Baltic Sea region, specifically Finnish and Swedish stakeholders. These might vary from other geographical contexts.